An annual profile of the impacts of simulated oil spills on the Northeast Arctic cod and haddock fisheries. (November 2022) - Carroll, JoLynn; Frøysa, Håvard G.; Vikebø, Frode; Broch, Ole Jacob; Howell, Daniel; Nepstad, Raymond; Augustine, Starrlight; Skeie, Geir Morten; Bockwoldt, Mathias
Abstract: We simulate the combined natural and pollutant-induced survival of early life stages of NEA cod and haddock, and the impact on the adult populations in response to the time of a major oil spill in a single year. Our simulations reveal how dynamic ocean processes, controlling both oil transport and fate and the frequency of interactions of oil with drifting fish eggs and larvae, mediate the magnitude of population losses due to an oil spill. The largest impacts on fish early life stages occurred for spills initiated in Feb–Mar, concomitant with the initial rise in marine productivity and the earliest phase of the spawning season. The reproductive health of the adult fish populations was maintained in all scenarios. The study demonstrates the application of a simulation system that provides managers with information for the planning of development activities and for the protection of fisheries resources from potential impacts. Highlights: We simulate major oil spills in the spawning areas of Northeast Arctic cod and haddock. Spills initiated in February–March result in the lowest survival percentages for fish larvae. The reproductive health of the adult populations is maintained in all scenarios. These simulations can assist managers in protecting fisheries from potential impacts.